Strategic Management in Developing Inclusive Teacher Career Paths: Optimizing Potential and Performance in Educational Institutions - Rifka Jannatul Firdausiyah; Unzilah Khomairohtusshiyamah; Zohaib Hassan Sain (Journal of Psychological Insight, 2026)
This study examines how to use strategic management to build inclusive teacher career paths. The aim of this research is to improve the potential, motivation, and performance of educators in educational institutions. Data were collected using descriptive qualitative methods through observations, interviews, and documentary research with principals, teachers, and management staff. The research shows that strategic management, which encompasses the steps of planning, implementing, evaluating, and adjusting strategies, has the potential to create a directed, equitable, and sustainable career system. Performance-based reward systems, mentoring, and training provide all teachers with equal opportunities to develop in inclusive career paths. This approach enhances the competitiveness and quality of educational institutions, in addition to improving teacher satisfaction and professionalism. Challenges such as lack of digitalization, limited resources, and fear of change still need to be addressed. Therefore, strategic management is an essential foundation for humanistic, inclusive, and sustainable standards-oriented teacher career management.